1990
DOI: 10.1007/bf02563825
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of fluoride on the secretion of insulin

Abstract: The oral administration of sodium fluoride (NaF) (40 mumol/100 body weight [bw]) to fasting rats produced an immediate fall in insulin levels and the consequent increase in glycemia. These phenomena were observed with plasma fluoride concentrations 5-15 microM. Glycemia and insulin returned to normal levels within 4-5 hours, together with the washing out of fluoride from plasma and soft tissues. The insulin secretion of isolated Langerhans islets, perifused with solutions containing 5, 10, or 20 microM fluorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
4

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 16 publications
5
31
0
4
Order By: Relevance
“…Previously it had been reported that chronic fluorosis caused alveolar hemorrhage, congestion, oedema fluid, necrosis of alve- ly increased lipid peroxidation in lung tissues of F1 rats, resulting in the increased olar epithelium distortion of alveolar architecture and bronchiolitis in the lung tissues of rats (23,25). In the present study, in F1 rats, alveolar congestion, descuamation of alveolar epithelium, thickened interalveolar septae were observed.…”
Section: Group Fluoride (Ppm)supporting
confidence: 59%
“…Previously it had been reported that chronic fluorosis caused alveolar hemorrhage, congestion, oedema fluid, necrosis of alve- ly increased lipid peroxidation in lung tissues of F1 rats, resulting in the increased olar epithelium distortion of alveolar architecture and bronchiolitis in the lung tissues of rats (23,25). In the present study, in F1 rats, alveolar congestion, descuamation of alveolar epithelium, thickened interalveolar septae were observed.…”
Section: Group Fluoride (Ppm)supporting
confidence: 59%
“…The development of glucose intolerance depends on both the duration and dose of exposure to F [7], [8]. Oral ingestion of F leads to transient inhibition of insulin secretion in both rats and humans [9]. Impairment of glucose homeostasis occurs when plasma levels of F exceed 5 µM.…”
Section: Introductionmentioning
confidence: 99%
“…Results are expressed as mean ± SE. *Significant differences compared to rats with access to drinking water containing 0, 1, and 5 ppm F (ANOVA, Tukey's post hoc test, p<0.05) fluoride intakes ranging between 0.2 and 2 mg/kg body weight, which is 40-4 times lower than the values of intake reported in previous experiments [6,7].…”
Section: Discussionmentioning
confidence: 54%
“…This effect was observed when plasma fluoride concentration is higher than 5 μM after a single dose of NaF in rats (7.6 mg F/kg body weight) and in humans (60 mg NaF) [6] and also after the administration of drinking water with fluoride 100 ppm to rats for 30 days [7]. The effect appears not to be related to insulin resistance [8], and it disappears when rats have high bone fluoride content, which is consistent with low plasma and tissue fluoride levels [7].…”
Section: Introductionmentioning
confidence: 96%